IDENTIFIKASI LAHAN BAGI PENGEMBANGAN TANAMAN JAHE (Zingiber offlcinale Rose.) DAN MELINJO (Gnetum gnemon L.) - Dedi Soleh Effendi (BERITA BIOLOGI, 2000)
Ginger (Zingiber officinale Rose.)and melinjo (Gnetum gnemon L) are potential comodities that have great opportunity to be promoted.Ginger is one of nine spices in international trade (and its market is also available in Indonesia and foreign market),while melinjo is known for long time and has high economic value. One important in promoting both comodities had to be known land potency in which both comodities would be cultivated.Land identification would be base on soil analysis in the laboratory,land ability map and field observation. Evaluation of soil fertility criteria and land suitability based on TOR Classification of land ability from Center Research of Soil and Agroclimate.Evaluation of soil chemical properties include N-toial, P-available, exchangeable potassium, cation exchange capacity, pH, and C-organic content.Evaluation of soil physical properties include soil-texture, drainage, soil effective depth and climate.The aim of this study was to observe real/current and potential land suitability level for ginger and melinjo in Lebak District.The result showed that land potency for promoting ginger and melinjo were 89 ha and 71 - 98 ha respectively.